GROWTH MONITORING OF SAND LOBSTER (Panulirus homarus) USING THE BOTTOM CAGE METHOD IN THE EXAMPLE UNIT OF MARINE LOBSTER CULTIVATION, BANYUWANGI REGENCY, EAST JAVA PROVINCE - Asep Akmal Aonullah (Universitas Tidar, 2022)
With the high demand for sea lobster as the industry has developed, Indonesia has an opportunity to establish the world's largest lobster aquaculture production. Therefore, a study related to the growing-out of lobster and also the development of engineering technology of lobster enlargement is needed. This study aims to determine the growth performance of Panulirus homarus reared in a bottom cage method. Lobsters with an average size of 116,25 g were reared for 150 days and fed with trash fish of 3%-4% of the biomass daily. The results showed that the use of the bottom cage method had positive effects on the survival rate, average body weight, specific growth rate dan food conversion ratio was 85%, 170 g, 0.25 g per day and11.16 respectively. The water quality is also was still within the suitable range for lobster rearing.